Case Method: Strategy For Improving The Capability Of Developing Teaching Modules Towards Differentiation Learning - Jarot Tri Bowo Santoso; Margunani; Moch Faizal Rachmadi; Muhammad Dwilian Fathurrohman; Naim Devitrisia (Indonesian Journal of Devotion and Empowerment, 2024)
The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia continues to strive for renewal and adaptation, including in the field of education. One way is by Implementing the Independent Curriculum (IKM). The IKM is an effort to catch up on learning losses due to the COVID-19 pandemic by returning school and local government authorities to manage their own education in accordance with conditions in their area. Even so, there are still many obstacles and confusion, especially for teachers in preparing for the learning process, one of which is in the education unit area of Semarang Regency. Teachers still do not optimally know the Learning Outcomes (CP), the formulation of Learning Objectives (TP), the preparation of Learning Objectives Flow (ATP) from Learning Objectives (TP), and the design of Teaching Modules. This service focuses on preparing differentiated teaching modules as a form of IKM acceleration. The method used is to conduct a workshop on preparing differentiated teaching modules based on the case method, followed by assistance in pre- and post-activity and program evaluation monitoring. This program targets partners, namely economics teachers, who are members of the Economics Subject Teacher Consultation (MGMP) throughout Semarang Regency. The results of this activity showed that teachers were very interested and able to improve the skills and understanding of teachers in preparing differentiated modules. The suggestion for this activity is that the relevant agencies always provide training in preparing differentiated teaching modules until all teachers follow, and in the future, it is hoped that the relevant parties and many universities will carry out evaluation training in the independent curriculum.